Consolidation of democracy in Indonesia: the issues and developments after political reform in 1998 - Satriawan, Iwan; Mokhtar, Khairil Azmin (2014)
After political reform in 1998 Indonesia has made many efforts and significant progress to establish a truly democratic government. This paper highlights some progressive democratic changes in Indonesia since 1998. The paper is based on doctrinal research with qualitative method. The result of research shows that there are some important democratic changes have been achieved. Three matters shall be highlighted in this paper. Firstly, the principle of democratic state based on the rule of law has been formulated clearly in the 1945 Constitution after amendment. The experience of bureaucratic-authoritarian system in Soeharto regime has given a meaningful lesson for Indonesia to create a more democratic country based on rule of law. Secondly, Indonesia had successfully gained the democratic transition which proved by the successful general elections in 1999, 2004 and 2009. This successful democratic election has made Indonesia been recognized as one of the largest democratic country in the world. Thirdly, despite the events and developments mentioned earlier some political experts argue that even though Indonesia’s democracy is on the right track, it is a muddled democracy because the battles among the political actors create stagnancy to political and economic developments. Politicians, civil society and the military are obviously the important elements which may influence the consolidation of democracy in Indonesia. It is concluded that in term of consolidation of democracy, further steps need to be taken to continue the process consolidation towards becoming a mature democracy.